RISK FACTORS ASSOCIATED WITH PULMONARY TB INCIDENCE IN CHILDREN IN BANDA ACEH - Riska Novita; Asnawi Abdullah; Hermasnyah Hermasnyah (Jukema (Jurnal Kesehatan Masyarakat Aceh), 2021)
Background: Pulmonary TB in children is still a serious public health problem in Aceh Province, this can be seen from the increase in cases in the last three years that are suspected to be related to immunization status, nutritional status, income, knowledge, the presence of TB sufferers, occupancy density and exposure to cigarette smoke. This study aims to determine the risk factors associated with pulmonary TB incidence in children in Banda Aceh. Method: This research is an analytic observational study using a case control design. The population in this study was children suffering from pulmonary TB in Banda Aceh as many as 30 respondents. Using a ratio of 1:2 comparison, the research sample of 90 respondents consisted of 30 cases and 60 controls.  Data collection was conducted from 15 October to 15 December, conducted in the respondent's home. Data analysis using conditional multiple logistic regression test. Results: Risk factors associated with pulmonary TB in childrenare: the employment of self-employed fathers (p=0.046; OR=2.7; 95% CI: 1.01-7.50), low income (p=0.046; OR=2.7; 95% CI: 1.01-7.50), the presence of TB patients in home (p=0.001; OR=31; 95% CI: 4.11-234), cigarette smoke exposure (p=0.004; OR=4; 95% CI: 1.54-10.3), no BCG immunization (p=0.023; OR=4.6; 95% CI: 1.23-17.2), malnutrition status with the occurrence of pulmonary TB in children in Banda Aceh (p=0.002; OR=5.9; 95% CI: 1.93-18.5). The results of the multivariate analysis concluded that the tendency of pulmonary TB in children in the city of Banda Aceh to occur in the presence of TB patients at home was almost 4 times more dominant than other variables. Recommendation: To Banda Aceh Health Office in order to increase the number of pulmonary TB screening in children, especially in children with parents who suffer from pulmonary TB.